Une traduction qui fait un manifeste. Art poétique de Verlaine et Sztuka poetycka de Miriam - Łukaszyk, Ewa (Romanica Silesiana)
The Polish translation of Verlaine’s Art poétique marks an important step in the process of acquisition of symbolism as a new paradigm of poetic creation. The analysis presented in this paper puts in the limelight the problem of positioning the translated text in the receptive literary system. The analytic proposal implies the employment of the term “embeddedness,” originally introduced by the historian Karl Polanyi, to render the implication of the non-economic factors in the process of production. Analogically, the production of literary texts is conditioned by factors situated at the frontier of literature. Those wishing to adopt a foreign aesthetics must vanquish the resistance of the local, traditionalist context. As a result, the translation is “embedded” as a manifesto, even if Verlaine’s Art poétique is a parody of the genre and an expression of the poet’s creative doubts rather than a truly prescriptive text. The auto-ironic dimension of the original poem disappears in the Polish translation by Miriam, which becomes a rigorous ars poetica.